Hitler Youth : growing up in Hitler's shadow - Bartoletti, Susan Campbell (New York : Scholastic Nonfiction, 2005)
The story of a generation of German young people who devoted all their energy to the Hitler Youth and the propaganda that brought Hitler his power, and the youths that resisted the Nazi movement. "I begin with the young. We older ones are used up. But my magnificent youngsters! Look at these men and boys! What material! With them, I can create a new world."-Adolf Hitler, Nuremberg,1933. By the time Hitler became Chancellor of Germany in 1933, 3.5 million children belonged to the Hitler Youth. It would become the largest youth group in history. Susan Campbell Bartoletti explores how Hitler gained the loyalty, trust, and passion of so many of Germany's young people. Her research includes telling interviews with surviving Hitler Youth members.
The bloody handprint: The murder of Herbert Norkus -- "For the flag we are ready to die": Hitler's rise to power -- "The brown pest": Organizing the Hitler youth -- "Where one burns books": A Nazi education -- "This thing about the Jews": Nazi persecution of the Jews -- "Muscle-tearing hard work": Preparing for war -- "Body and soul": The German war machine -- "Serving a mass murderer": The Holocaust begins -- "Long live freedom!": Hitler youth and resistance -- "Fanatical fighters": Hitler's boy soldiers, 1943-1945 -- "I could not help but cry."
Includes bibliographical references (p. 169-173) and index.
Keywords: Hitler-Jugend -- Juvenile literature; Hitler-Jugend.; National socialism and youth -- Juvenile literature; Jewish youth -- Germany -- History -- 20th century -- Juvenile literature; Holocaust, Jewish (1939-1945) -- Germany -- Juvenile literature; Jewish children in the Holocaust -- Juvenile literature; National socialism and youth; Jewish youth -- Germany -- History -- 20th century; Holocaust, Jewish (1939-1945) -- Germany; Jewish children in the Holocaust